Decreased Sperm Motility in Rats Orally Exposed to Single or Mixed Pesticides - Perobelli, Juliana Elaine; Martinez, Meire Franca [UNESP]; da Silva Franchi, Carla Adriene [UNESP]; Fernandez, Carla Dal Bianco; Camargo, João Lauro Viana de [UNESP]; Kempinas, Wilma de Grava [UNESP] (Taylor & Francis Inc, 2010)
The Brazilian Agency of Sanitary Vigilance (ANVISA) conducted a study that demonstrated the presence of residues of several pesticides in fresh fruits and vegetables that were available for purchase by the general populace. In order to evaluate potential adverse health effects of low-level exposure to agrochemicals, the reproductive toxicity of the pesticides dicofol, dichlorvos, permethrin, endosulfan, and dieldrin was evaluated in rats dosed with these chemicals individually or as mixtures. Sixty male Lewis rats (6 wk old, 200 x g) were randomly allocated to 8 groups: (1) control group, received basal diet; (2) 5 groups designated a to e received the diet containing each pesticide individually, at the respective effective doses: lowest-observed-adverse-effect level (LOAEL) for dieldrin and endosulfan, lowest-observed-effect level (LOEL) for dicofol, and lowest effect level (LEL) for dichlorvos and permethrin, respectively, depending on the published data; (3) effective dose group, which received a mixture of pesticides added to basal diet at the respective doses reported to produce adverse effects; and (4) low dose group, which received a pesticide mixture added to the basal diet, where each pesticide was at its no-observed-effect level (NOEL). After 8 wk of treatment, reproductive parameters were evaluated. Sperm morphology, daily sperm production (DSP), sperm transit time through the epididymis, hormonal levels, and histopathological evaluation of testis and epididymis did not differ significantly among the groups. However, sperm motility was significantly decreased in animals that received a mixture of dieldrin, endosulfan, dicofol, dichlorvos, and permethrin, as well as in the group receiving dicofol alone. Exposure to the individual pesticides endosulfan, dichlorvos, and permethrin did not markedly affect sperm motility. The impairment of sperm motility in the mixture of pesticides at the NOEL level indicates that reproductive effects not seen with individual pesticides may occur in presence of several pesticides due to an additive effect. However, the pesticide mixtures did not appear to affect DSP or spermatogenesis despite reduced sperm motility.